The Profession of Female Non-Judicial Mediators in Gender Mainstreaming in District Courts on The Island of Java - Lusianawati, Hayu; Sunarsi, Dessy (Asosiasi Pusat Studi Wanita/Gender & Anak Indonesia (ASWGI), 2025)
Supreme Court Regulation (PERMA) No. 1 of 2016 concerning Mediation Procedures in Courts stipulates that all civil disputes in the First Instance Court must first be resolved through peace with the assistance of a mediator. The success of mediation in District Courts in Java is supported by certified non-judge mediators. Female non-judge mediators have the same role as male non-judge mediators. This study aims to analyze the role of the profession of female non-judge mediators in gender mainstreaming in District Courts in Java. A non-judge mediator is someone who acts as a liaison between disputing parties in the justice system. However, their role in ensuring gender equality and overcoming gender bias has not been widely explored. This research is descriptive qualitative, supported by primary data by conducting observations and data tracing in the field. Data were collected related to perceptions of gender equality, the challenges faced, and the practices they apply in mediation. The results of this study indicate that female non-judge mediators have varying awareness of gender issues. Some have taken steps to ensure equality in the mediation process, such as ensuring active participation of both parties and avoiding gender stereotypes. However, challenges remain, including a lack of specific training on gender mainstreaming and a lack of institutional support. This study provides recommendations to enhance the role of female non-judicial mediators in creating a more inclusive and equitable mediation environment. More rigorous training, practice guidelines, and support from the courts as well as relevant institutions are needed to ensure that female non-judicial mediators can effectively promote gender equality in the mediation process.